Recycling phosphate mine waste rocks in asphalt mixtures to fully replace natural aggregate: A preliminary study - Fadi Alhomaidat; Mazen J. Al-Kheetan; Sajedah M. Alosifat (Results in Engineering)
Mining activities generate large quantities of waste rocks that pose significant challenges to the environment due to their disposal in landfills, making their incorporation in asphalt mixtures a vigorous solution. This work offers a groundwork for assessing the effectiveness of fully replacing natural limestone aggregate with phosphate mine waste rocks (PMWR) aggregate in asphalt mixtures. The mixtures’ mechanical, microstructural, and synergistic properties were evaluated using the cantabro test, scanning electron microscopy (SEM) analysis, and the attenuated total reflectance-fourier transform infrared spectroscopy (ATR-FTIR) analysis, respectively. The complete replacement of limestone with PMWR aggregate resulted in a mixture with 20 % cantabro loss compared to 17 % cantabro loss for the limestone mixture. The morphology of the PMWR asphalt mixture revealed the formation of wide cracks and the development of a weak interfacial transition zone between the aggregate and the asphalt binder. Meanwhile, the limestone mixture showed a good bonding between the limestone and the asphalt binder, resulting in a more robust and stable mixture. Moreover, higher intensities for the Si–O–Si and Si–O bonds were observed in the limestone mixture compared to the PMWR mixture. In contrast, PO4–3 bonds were developed in the PMWR mixture with their absence in the limestone mixture, which confirms the superior performance of the limestone mixture due to the negative effect of high phosphate levels on the rheology of the asphalt binder. Results from this study can pave the way for further research to optimize the integration levels of PMWR aggregates in asphalt mixtures.